STRATEGI PEMERINTAH DESA PADANG TANGGUNG KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI DALAM UPAYA MENGEMBANGKAN OBYEK WISATA PANTAI JAI JAI RAOK TAHUN 2019-2020 - Roki Pahwanzi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Jai jai Raok Beach tourism object is a beach-style tourist destination consisting of a stretch of white sand and coconut trees that makes this place similar to the beach in general. Jai jai raok beach is located in the village of Padang Responsibility Pangean District, Kuantan Singingi Regency. In 2019 where this tourist attraction is very much in demand by visitors until 2020, the number of visitors every year has increased, but in fact the existing facilities at the Jai-jai Raok Beach tourism object which is managed by BUMDes Rajo Bujang, Padang Responsibility Village are still minimal in facilities or infrastructure. infrastructure in Jai-jai raok beach tourism so that there is a need for improvement in the management and development of Jai-jai raok beach tourism. This study aims to determine the strategies and inhibiting factors for the development of tourism potential of Jai jai Raok Beach, Padang Respons Village, Pangean District, Kuantan Singingi Regency. This study uses descriptive qualitative methods and data collection techniques based on observations, literature studies and interviews. The results of this study indicate that the Padang Responsibility Village Government Strategy, Pangean District, Kuantan Singingi Regency in developing Jai jai Raok Beach Tourism is still not optimal. This can be seen from the strategies and efforts that have been made by the Village Government as a tourist attraction management agency that has not fully implemented and implemented the village government's strategy because it only implemented the strategy after the budget was entered. Jai jai Raok in Padang Responsibilities consists of internal factors and external factors. The internal factors that become obstacles in the management of Jai jai Raok Beach Tourism Objects in Padang Responsibility are limited funds, inadequate human resources and regulations. Meanwhile, the external factors that become obstacles are the low involvement of the private sector in the development of tourism objects. Keywords: Village Government Strategy, Tourism Object Development